Strategi Pemasaran Jasa Pendidikan Dalam Meningkatkan Peminat Dan Daya Tarik Untuk Menyekolahkan Anak Ke SD Muhammadiyah 3 Nusukan Surakarta - Pertiwi, Ade Arum; , Drs. H. Mulyadi Sri Kamulyan,S.H, M.Pd (2017)
Along with the development of competition between educational institutions increasingly competitive. But the appeal of the community to send their children to Muhammadiyah Elementary School 3 of Nusukan Surakarta not even recede. Seeing this phenomenon researchers interested in studying more about the marketing strategies of educational services in increasing interest and appeal to send children to Muhammadiyah Elementary School 3 of Nusukan Surakarta. This study aims to investigate the implementation of the marketing strategy of educational services, supporting factors and obstacles in the implementation of marketing strategies in order to increase interest in educational services and public appeal to send their children to Muhammadiyah Elementary School 3 of Nusukan Surakarta. This type of research is research kualiatif. The approach used a qualitative approach with a qualitative research design bersisfat descriptive phenomenology. Data collection techniques using the method of observation, interviews, and documentation. The validity of the data by triangulation. Data analysis techniques with data reduction, data presentation, and concluded. This study addressed two subjects, namely the implementation of the marketing strategy of educational services, supporting factors and obstacles in the implementation process. The process of implementation of the marketing strategy of educational services performed Muhammadiyah Elementary School 3 of Nusukan Surakarta namely: identification and analysis of market, segmentation and positioning, differentiation, promotion, promotion evaluation. Factors supporting namely Fiduciary community and alumnus still relatively high. Inhibiting factors namely: time and human resources.